Personal debt in Europe : the EU financial market and consumer insolvency / Federico Ferretti, Daniela Vandone. - Ferretti, Federico, 1970-; Vandone, Daniela (Cambridge University Press, 2019)
Personal debt remains an important factor in many economic models because it encourages people to use debt to finance consumption. Whether this model is sustainable for individuals or the countries in which they reside is an ongoing question of great complexity and many social and economic implications, not only for the burdened individuals and their countries, but also for the EU as a whole. In Personal Debt in Europe, Federico Ferretti and Daniela Vandone examine the 'dark side' of personal debt, or over-indebtedness, in social and economic terms. They employ cross-country consumer-level data to present the latest empirical studies on the problem, analyse these findings to better understand its nature and causes, and discuss the merits of proposed insolvency legislation and harmonisation initiatives in the EU.